2022
DOI: 10.1186/s12903-022-02318-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of BMI with the diet, physical activity and oral hygiene practices amongst the dental students

Abstract: Background Regardless of attaining adequate knowledge regarding oral hygiene, physical activity, and healthy eating habits, dental students still face oral health problems. This study was aimed to assess the association of oral hygiene habits, physical activity, and eating habits with the BMI in the dental students. Method This multi centric cross-sectional study was conducted from January to May 2021 in Pakistan. Three hundred and eighty-six stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…Our results also show that body fat based on height and weight measured through BMI also linked significantly to the presence of dental caries, particularly with people with overweight/obesity having higher levels and are consistent with other studies [42][43][44]. It is possible that the increased experience of caries in the overweight and obese groups is due to other factors, such as dietary habits like the consumption of sugary drinks and foods [42,45]. However, even though the results of this study demonstrate a link between higher BMI Index and dental caries a more in-depth understanding of how obesity affects oral health, including dental caries, is necessary because there also findings that suggest a inverse relationship between dental caries experience and obesity [46,47].…”
Section: Discussionsupporting
confidence: 90%
“…Our results also show that body fat based on height and weight measured through BMI also linked significantly to the presence of dental caries, particularly with people with overweight/obesity having higher levels and are consistent with other studies [42][43][44]. It is possible that the increased experience of caries in the overweight and obese groups is due to other factors, such as dietary habits like the consumption of sugary drinks and foods [42,45]. However, even though the results of this study demonstrate a link between higher BMI Index and dental caries a more in-depth understanding of how obesity affects oral health, including dental caries, is necessary because there also findings that suggest a inverse relationship between dental caries experience and obesity [46,47].…”
Section: Discussionsupporting
confidence: 90%
“…This trend is particularly visible among individuals classified as overweight or obese, who generally show higher levels of tooth decay, a finding that aligns with other studies [49][50][51]. The increased rate of tooth decay in these groups may be related to the consumption of diets high in sugary drinks and food [52]. Although our study points to a correlation between higher BMI and dental cavities, the complex relationship between obesity and oral health, including tooth decay, warrants further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…High free-sugar intake is associated with dental caries, as well as increased weight and body mass index (BMI) [ 10 ]. Physical activity benefits to maintain normal BMI and health status, and however, the conclusions on the relationship between physical activity and dental caries are still ambiguous [ 11 , 12 ]. A mutual etiologic contributing factor between obesity and dental caries is diet high in sugar, where physical activity can burn off the supernumerary energy (mostly roots in carbohydrates) and reduce BMI, and may also be associated with the development of dental caries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity benefits to maintain normal BMI and health status, and however, the conclusions on the relationship between physical activity and dental caries are still ambiguous [ 11 , 12 ]. A mutual etiologic contributing factor between obesity and dental caries is diet high in sugar, where physical activity can burn off the supernumerary energy (mostly roots in carbohydrates) and reduce BMI, and may also be associated with the development of dental caries [ 12 ]. It is worth noting that a systematic review has shown that Ca intake and physical activity may have a combined effect on bone mineral density (BMD) in children and adolescents, that is, in the case of adequate Ca intake, a higher level of physical activity may contribute to bone mass accumulation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%